ANALYZING STUDENT WRITING: A COMPREHENSIVE STUDY OF SOCIOLINGUISTICS, SYNTAX, AND VOCABULARY - Ikrimah; Asi, Natalina (International Journal of Social Science, 2024)
This study presents a comprehensive analysis of an English analytical exposition text written by Indonesian students on "The Dangers of Smoking." By evaluating the text using three key criteria – Sociolinguistics, Syntax, and Vocabulary – the researchers aim to explore the students' ability to utilize language in social contexts, their understanding of sentence structure, and their proficiency in using suitable words to convey their arguments effectively. Through a qualitative approach, the researchers conducted a meticulous assessment of the text, revealing the students' adeptness in incorporating societal implications, utilizing logical sequencing, and employing persuasive language. The findings of this study offer valuable insights into students' written capabilities and provide guidance for future pedagogical interventions in fostering linguistic development among learners.